IMPLEMENTATION OF DESIGN THINKING FOR THE DIGITAL TRANSFORMATION OF DESA CANTIK MENTORSHIP AT BPS-STATISTICS TANGERANG REGENCY - Reza Septian Pradana (PT. Radja Intercontinental Publishing, 2026)
Village for Statistical Excellence or Desa Cinta Statistik (Desa Cantik) program is a sectoral statistical development program implemented by the BPS-Statistics Indonesia to improve literacy, data management quality, and statistical utilization at the village level. However, the implementation of face-to-face statistical development still faces various obstacles, such as limited learning time, a work environment full of interruptions for village officials, difficulty repeating material, and limited access to flexible learning media. This study aims to design a digital transformation of Desa Cantik development program at the BPS Tangerang Regency using a design thinking approach. The study used a qualitative approach with the stages of understand, observe, define point of view, ideate, prototype, test, and reflect. Data collection was conducted through in-depth interviews, observation, documentation, and usability testing with village statistical agents assisted by BPS Tangerang Regency. The results showed that village statistical agents need statistical learning media that is simple, flexible, easily accessible, and can be re-learned independently. Based on the results of the ideation and testing process, a prototype of an Android-based e-learning application called StaT-Gem (Statistik Tangerang Gemilang) was developed, which features short learning videos, a structured material repository, an offline mode, and light quizzes with positive feedback. Usability testing results indicate that the application is easy to use, has intuitive navigation, and can help users access learning materials more flexibly according to the working conditions of village officials. This study concluded that the application of design thinking can produce digital transformation solutions that are more adaptive to user needs and support the sustainability of Desa Cantik's statistical development through an effective and user-centered e-learning approach.